2017
DOI: 10.3390/molecules22071056
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Microwave-Assisted Extraction of Polyphenols from Olive Tree Leaves: Antioxidant and Antimicrobial Properties

Abstract: Response surface methodology (RSM) and artificial neural networks (ANN) were evaluated and compared in order to decide which method was the most appropriate to predict and optimize total phenolic content (TPC) and oleuropein yields in olive tree leaf (Olea europaea) extracts, obtained after solvent-free microwave-assisted extraction (SFMAE). The SFMAE processing conditions were: microwave irradiation power 250–350 W, extraction time 2–3 min, and the amount of sample 5–10 g. Furthermore, the antioxidant and ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(83 citation statements)
references
References 44 publications
6
74
0
3
Order By: Relevance
“…Olive leaves, an agricultural waste obtained during harvesting or processing of olive fruits, contain significant amounts of valuable compounds such as phenolic compounds, which have attracted considerable interest due to their potential use as food additives and/or nutraceuticals in both food and pharmaceutical industries (Le Floch, Tena, Ríos, & Valcarcel, ; Moubarik et al, ; Roselló‐Soto, Barba, et al, ; Roselló‐Soto, Koubaa, et al, ; Şahin et al, ). The polyphenol profiles of olive leaves are different depend on their distribution in various regions (Özcan & Matthäus, ).…”
Section: Introductionmentioning
confidence: 99%
“…Olive leaves, an agricultural waste obtained during harvesting or processing of olive fruits, contain significant amounts of valuable compounds such as phenolic compounds, which have attracted considerable interest due to their potential use as food additives and/or nutraceuticals in both food and pharmaceutical industries (Le Floch, Tena, Ríos, & Valcarcel, ; Moubarik et al, ; Roselló‐Soto, Barba, et al, ; Roselló‐Soto, Koubaa, et al, ; Şahin et al, ). The polyphenol profiles of olive leaves are different depend on their distribution in various regions (Özcan & Matthäus, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, however, it was shown that the maximum response in hesperetin/AA mixtures was achieved at a molar ratio of 5.2/1, which clearly indicated that the nature of polyphenolic antioxidant may define the molar ratio that could yield maximum antioxidant effect, in combination with AA. Furthermore, other authors supported that compounds that are co-extracted with polyphenols from OLL could also interfere [29], but such an effect remains to be elucidated. …”
Section: Discussionmentioning
confidence: 99%
“…(5) (5) where X 1 is the amount of sample, X 2 is the MW irradiation power, and X 3 is the extraction time [9].…”
Section: Phenolic and Antioxidant Compound Extraction From Plant Matementioning
confidence: 99%
“…(4) [9] Yield = 0.62767 − 0.029622 X 1 − 2.60 × 10 Where X 1 is the amount of sample, X 2 is the Microwave (MW) irradiation power, and X 3 is the extraction time. The researchers found that the second power of microwave intensity was the most significant parameter, followed by the amount of sample, quadratic time, and power for oleuropein yield [9].…”
Section: Yieldmentioning
confidence: 99%
See 1 more Smart Citation